2015
DOI: 10.1128/aac.01733-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility Profiles of Eight Antifungal Drugs against Clinical and Environmental Strains of Phaeoacremonium

Abstract: hIn vitro susceptibilities of a worldwide collection of molecularly identified Phaeoacremonium strains (n ‫؍‬ 43) belonging to seven species and originating from human and environmental sources were determined for eight antifungal drugs. Voriconazole had the lowest geometric mean MIC (0.35 g/ml), followed by posaconazole (0.37 g/ml), amphotericin B (0.4 g/ml), and isavuconazole (1.16 g/ml). Caspofungin, anidulafungin, fluconazole, and itraconazole had no activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…In fact, the full range of species against which isavuconazole has activity and the clinical breakpoints have not yet been established. Nevertheless, previous studies have demonstrated MIC values of ≤4 μg/mL for many species closely related or identical to the rare pathogens in the current study . Although some isolates in the current study appeared to have reduced susceptibility in vitro compared with those prior studies, we cannot exclude the possibility of cross‐resistance in some patients who failed prior antifungal therapy.…”
Section: Discussioncontrasting
confidence: 74%
“…In fact, the full range of species against which isavuconazole has activity and the clinical breakpoints have not yet been established. Nevertheless, previous studies have demonstrated MIC values of ≤4 μg/mL for many species closely related or identical to the rare pathogens in the current study . Although some isolates in the current study appeared to have reduced susceptibility in vitro compared with those prior studies, we cannot exclude the possibility of cross‐resistance in some patients who failed prior antifungal therapy.…”
Section: Discussioncontrasting
confidence: 74%
“…The in vitro susceptibility profile of Phaeoacremonium parasiticum has been proposed by Badali et al [ 20 ] and shows a similar pattern with Phaeoacremonium parasiticum isolated from the cornea of our patient. Phaeoacremonium parasiticum showed a low MIC for amphotericin B, voriconazole and posaconazole.…”
Section: Discussionsupporting
confidence: 87%
“…has been found to be more susceptible in vitro than Fusarium spp. [ 23 ]. This finding prevented unnecessary combination anti-fungal therapy and simplified the regimen for the patient.…”
Section: Resultsmentioning
confidence: 99%